2015
DOI: 10.1016/j.neuropharm.2015.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the prostaglandin EP2 receptor is neuroprotective and accelerates functional recovery in a rat model of organophosphorus induced status epilepticus

Abstract: Exposure to high levels of organophosphorus compounds (OP) can induce status epilepticus (SE) in humans and rodents via acute cholinergic toxicity, leading to neurodegeneration and brain inflammation. Currently there is no treatment to combat the neuropathologies associated with OP exposure. We recently demonstrated that inhibition of the EP2 receptor for PGE2 reduces neuronal injury in mice following pilocarpine-induced SE. Here, we investigated the therapeutic effects of an EP2 inhibitor (TG6-10-1) in a rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
121
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(145 citation statements)
references
References 37 publications
21
121
3
Order By: Relevance
“…We have previously shown that, during the 24 h following SE, rodents quickly lose 10-20% of their body weight and then gradually begin to recover in the following days (6,8,39). As expected, animals subject to SE lost ∼13% of their body weight in the 24 h after SE onset, independent of Ccr2 genotype (Fig.…”
Section: Ccr2 Ablation Enhances Weight Regain and Reduces Hippocampalsupporting
confidence: 77%
See 3 more Smart Citations
“…We have previously shown that, during the 24 h following SE, rodents quickly lose 10-20% of their body weight and then gradually begin to recover in the following days (6,8,39). As expected, animals subject to SE lost ∼13% of their body weight in the 24 h after SE onset, independent of Ccr2 genotype (Fig.…”
Section: Ccr2 Ablation Enhances Weight Regain and Reduces Hippocampalsupporting
confidence: 77%
“…These admittedly sparse clinical findings are consistent with the much more extensive animal literature in demonstrating a florid inflammatory response of the brain to SE (5). We and others have provided evidence in animal models of epilepsy that quenching inflammation after SE can provide neuroprotection, prevent BBB opening, alleviate morbidity, and rescue behavioral deficits (6)(7)(8)(9)(10).…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Targeting EP2 signaling pathways may be an efficient approach to control the degree of microglial activation, thus reducing chronic inflammation and brain damage in neurologic diseases. The therapeutic window for EP2 antagonists opens after seizures with the neuronal induction of COX-2 and consequent production of PGE 2 Rojas et al, 2015). Our data suggest that the therapeutic window might close toward the end of active inflammation, when microglial death is needed to resolve inflammation.…”
Section: Ep2 Promotes Microglia Deathmentioning
confidence: 79%